Evidence Based Study on Efficacy of LM Potency in PSORIASIS (Advancements in Homeopathic Research, 2022)
The Psoriaisis is one of the auto immune disease and in such kind of diseases there’s need to repeat the dose frequently without disturbing the natural pattern of disease and also avoid the unwanted aggravation. In some cases patient required the medicine frequently but we are afraid to repeat the dose though we need to repeat and sometimes we don’t judge when and how much to repeat the dose to give the relief to the patient. What I have experienced while dealing with these kind of psoriasis cases, sometimes with the help of the centesimal potency we see the primary action of the medicine and we see the slight improvement but after sometime the action of the medicine exhaust and even after repetition with the centesimal potency we cannot see the reliable improvement as it should have come though we repeat higher potency. Sometimes the action of the medicine is blocked and cannot stimulate the vital force and we cannot see the primary action of the vital force. And sometimes also vital force gets resisted by the same medicine in same potency and we cannot change the degree of the potency. So with the help of the 50 millesimal potency we can break the resistance of the vital force by changing the degree of the potency by succussing the medicinal liquid. And also repeat the medicine frequently as needed for the patient and we avoid the unwanted aggravation and give gentle and rapid cure to the patient. So with the help of the 50 millesimal potency we can achieve the cure and restore the health as it is termed.
Keywords: LM Potency; PSORIASIS; non-contagious disease